Flame-Front Rate of Spread Estimates for Moderate Scale Experimental Fires Are Strongly Influenced by Measurement Approach - Johnston, Joshua M.; Wheatley, Melanie J.; Wooster, Martin J.; Paugam, Ronan; Davies, G. Matt; DeBoer, Kaitlin A. (Fire (Basel, Switzerland), 2018)
Understanding wildfire rate of spread (RoS) is often a key objective of many fire behavior modelling and measurement exercises. Using instrumented moderate scale laboratory burns we provide an assessment of eight different methods of flame front RoS determination, including visible imagery (VIS) analysis techniques, use of thermocouple arrays, and four thermal infrared (IR) image analysis approaches. We are able to (1) determine how measurement approach influences derived RoS, and (2) recommend the best method to reproduce the accepted standard (Thermocouple Grid Array measurement) RoS without ground sampling. We find that derived RoS is statistically significantly influenced by the measurement approach, and that failing to fully account for directionality of the RoS may result in significant error. We identify one of the thermal infrared imaging methods (described in Paugam et al. 2013), as the most appropriate for providing rate and direction of spread at these scales of measurement.